Association of sports drinks with weight gain among adolescents and young adults. (14th July 2014) - Field, Alison E.; Sonneville, Kendrin R.; Falbe, Jennifer; Flint, Alan; Haines, Jess; Rosner, Bernard; Camargo, Carlos A.
<x xml:space="preserve">Abstract</x> Objective Sales of regular soda were declining, but sales of other sweetened beverages, such as sports drinks, were increasing. Our objective was to determine the prospective associations between sports drinks and body mass index (BMI) gains among adolescents and young adults. Methods 4121 females and 3438 males in the Growing Up Today Study II, aged 9‐16 in 2004, from across the United States were followed prospectively. Data were collected by questionnaire in 2004, 2006, 2008, and 2011. Servings per day of various beverages were assessed with a food frequency questionnaire. Results Among the girls, each serving per day of sports drink predicted an increase of 0.3 BMI units (95% confidence interval (CI) CI 0.03‐0.54) more than their peers over the next 2‐3 years. Among the males, each serving of sports drinks predicted a 0.33 BMI (95% CI 0.09, 0.66) increase. In addition, boys who increased their intake over the 2‐3 year interval gained significantly more than their peers during the same time interval. Conclusions Intake of sports drinks predicted larger increases in BMI among both females and males. Our results suggest that school policies focused on obesity prevention should be augmented to restrict sports drinks.